Production of the low-carbon structural steel 15NMFL on the basis of recycling of armor scrap - V. M. Gatsuro (Литьë и металлургия)
The received steel has the increased and stable impact elasticity^ good weldability and can be recommended for production of moulded pieces of specially critical assignment, being exploited in conditions of heavy loading at high impact and cyclic loads.